Awareness and practice of contraceptive methods among women in Kerala, India - Alukal, Anila Tresa; George, Lissiamma; Raveendran, Resmy C. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: India is the second most populous country in the world, sustaining 17.01% of world population on 2.4% of world’s surface area. Indian women have more children than desired and often too close together. Family Planning can have a positive impact on population growth, maternal mortality, and infant and new-born outcomes. In spite of availability of wide range of contraceptives, the unmet need for family planning is estimated to be 12.8%. The purpose of this study is to assess awareness of the effective use of contraceptive methods among pregnant women, which will provide useful information for future intervention strategies and the reduction of unwanted pregnancies. Methods: The study was conducted at the Government Medical College Thrissur, Kerala and study period was 1year (2014-2015). The awareness and contraceptive practices of 514 pregnant women who were admitted for delivery were assessed by using questionnaire. The data was entered in MS excel sheet and analysed using SPSS software. Results: the awareness regarding barrier method of contraception was maximum. (96.7%), followed by permanent methods (96.8%), IUCD (94.9%) and natural methods (92.6%). Around 71.6% of the study population has used some form of contraception. The most commonly contraceptive method was natural methods (69.6%) followed by barrier method (59.9%). IUCD was the method which was least practiced (2.9%) followed by OC pills (19.1%). Conclusions: Even though women are well aware of most of the contraceptive methods, the percentage of women using it is very low. This shows that there is good knowledge regarding contraceptive methods, but a change is needed in the attitude and practice.